Impact of Robotic Process Automation (RPA) on the Reporting Efficiency of Administrative Areas: A Systematic Review of the Literature - Palomino Inza, Patricia Delfina; Siqueros Romaní, Michael; Linares Grijalva, Karin Dessiré; Rodrigue Santos, Marycarmen (LACCEI, 2025)
Robotic Process Automation (RPA) has emerged as a transformative technology in enterprise reporting management, significantly improving operational efficiency and data accuracy. This systematic literature review aims to analyze the impact of Robotic Process Automation on the recurring generation of reports within administrative areas, with the purpose of evaluating how RPA can reduce human error rates and increase productivity compared to traditional methods. For this purpose, 324 articles were reviewed using the PRISMA automation in business management. methodology, selecting those that meet specific inclusion and exclusion criteria relevant to this study. The results obtained from the reviewed publications indicate that the implementation of Robotic Process Automation reduces human error and increases productivity in report generation, with improvements in data consistency and accuracy. Additionally, the importance of adequate training for employees interacting with RPA systems is highlighted, ensuring a smooth transition from manual processes and optimizing return on investment. Finally, it is concluded that although RPA has proven to be highly beneficial, its successful implementation depends on a combination of advanced technology and skilled human talent. The review suggests that future research should focus on the development of RPA in combination with Business Process Management to maximize the benefits of automation in business management